Geographic origin and the cardiovascular risk profile – The Cardiovascular Risk in Young Finns Study - Vähämurto, Lauri (fi=Turun yliopisto|en=University of Turku|, 2020)
Background: Since the 1940’s, coronary heart disease (CHD) has been recognized as a major cause of death in the developed countries. Men born in eastern Finland were found to have internationally high CHD mortality in the late 1960’s. As a result, the “North Karelia Project” was launched, aiming to decrease CHD risk factors especially in the high risk areas. Since then, CHD mortality rates have decreased significantly in Finland with over two thirds of the decline explained by favourable changes in modifiable risk factors. Despite the overall reduction, regional differences in the rates are still seen. Although regularly studied, the current regional differences in Finland in CHD risk factors and surrogate markers subclinical atherosclerosis are thoroughly investigated. Aims: This thesis aimed to investigate current and 31-year longitudinal CHD risk factors between eastern and western Finns, to examine east-west differences in subclinical atherosclerosis measured by carotid intima-media thickness (IMT) and in cardiac left ventricular (LV) structure and function, to explore CHD risk factors, carotid IMT and left ventricular structure and function between urban and rural Finns, and to study the association of migration with CHD risk factors and carotid IMT. Participants and methods: This thesis uses data from the Cardiovascular Risk in Young Finns Study which is a prospective multicentre cohort launched in 1980. CHD risk factors have been measured from the participants repeatedly since the baseline study. Carotid IMT was first measured in 2001 from the participants and echocardiography was included in 2011, when over 57% of the original study population participated in the latest follow-up study at the age of 34–49. Results: In 2011 CHD risk factor profile between participants with eastern or western baseline origin was essentially similar. However, eastern participants have excessive risk in longitudinal risk factor analyses and they have higher carotid IMT, LV mass and worse LV diastolic function than western participants. Participants with urban baseline origin have lower CHD risk factor levels and LVM compared to rural participants. Participants who migrated from east-to-west or rural-to-urban have currently lower CHD risk factor levels and carotid IMT compared to participants who stayed in east/rural areas, respectively. Conclusions: Differences between eastern and western Finns in CHD risk factor levels are levelling off but can still be found in carotid IMT, LV mass and diastolic function, and in longitudinal CHD risk factor analyses. Urban Finns have lower CHD risk factor levels compared to rural Finns. Migration from areas characterised by higher CHD risk factor levels is associated with improvements in cardiovascular health.